Ubezpieczenia jako element zarządzania finansami w świetle badania budżetów gospodarstw domowych - Dembowska, Barbara (Insurance products as a part of financial management in surveys of household budget, 2006)
This article presents an analysis of financial situation of household in Poland. There are used the results of research made from Central Statistical Office in Poland in 2001 and 2004. In the first part there are an analysis of net receipts and net outgoings. In the second part there are presents savings items on the receipt and outgoing side. The main part of this article is an analysis of expenditures on insurance, particular connected with the dwelling, with health and with transport.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 84-92